Role of noncoding RNA in the pathophysiology and treatment of intrauterine adhesion - Liu, Hui-Dong; Wang, Shao-Wei (Frontiers in Genetics, 2022)
Intrauterine adhesion (IUA) is one of the most common reproductive system diseases in women. It is often accompanied by serious clinical problems, which seriously damage reproductive function, such as menstrual disorder, infertility or recurrent abortion. The clinical effect of routine treatment is not ideal, and the postoperative recurrence rate is still very high. Therefore, it is urgent to explore the pathological mechanism of IUA and find new strategies for effective prevention and treatment. It is known that the main pathological mechanism of IUA is endometrial fibrosis and scar formation. Non-coding RNA plays an important role in the fibrosis process, which is one of the latest research advances in the pathophysiology of IUA. Moreover the exosomal miRNAs derived from mesenchymal stem cells(MSCs) can be used to improve intrauterine adhesion. This paper reviewed the role of ncRNAs in the pathogenesis of IUA, summarized the core pathways of endometrial fibrosis regulated by ncRNAs and finally introduced the potential of miRNAs as a therapeutic target.